2005
DOI: 10.1242/dev.01935
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hypoplasia and craniofacial defects in mice lacking heparan sulfateNdst1gene function

Abstract: Materials and methods Targeted recombination of the Ndst1 geneThe thymidine-kinase/neomycin containing targeting vector was constructed by insertion of loxP-sites in intron-sequences surrounding exon 2 (the first coding exon) of Ndst1. The final targeting vector was linearized using SalI before transfection of ES cells. R1 ES cells were grown, transfected and subjected to neomycin G418 selection. Homologous recombinants were identified by Southern blotting and PCR and transfected with a Cre-expressing vector, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
182
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(200 citation statements)
references
References 59 publications
13
182
0
Order By: Relevance
“…Of interest, Ndst1 mutant mice display developmental defects that mainly resemble those found in embryos made deficient for two families of growth factors: the Fgfs and Hhs (Table 1). Previously, we showed genetic interaction between Shh and Ndst1 and reduced Ptc expression in facial Ndst1 Ϫ/Ϫ mesenchyme as well as strongly reduced MAPK activity after Fgf-2 stimulation of Ndst1 Ϫ/Ϫ mesenchymal fibroblasts (Grobe et al, 2005). In this work, we confirmed impaired Fgf function in the developing mutant skull in agreement with the established role of Fgf-8 in skull and facial development (Meyers et al, 1998;Trumpp et al, 1999;Abu-Issa et al, 2002;Frank et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Of interest, Ndst1 mutant mice display developmental defects that mainly resemble those found in embryos made deficient for two families of growth factors: the Fgfs and Hhs (Table 1). Previously, we showed genetic interaction between Shh and Ndst1 and reduced Ptc expression in facial Ndst1 Ϫ/Ϫ mesenchyme as well as strongly reduced MAPK activity after Fgf-2 stimulation of Ndst1 Ϫ/Ϫ mesenchymal fibroblasts (Grobe et al, 2005). In this work, we confirmed impaired Fgf function in the developing mutant skull in agreement with the established role of Fgf-8 in skull and facial development (Meyers et al, 1998;Trumpp et al, 1999;Abu-Issa et al, 2002;Frank et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Also, as we and others (Ledin et al, 2004;Grobe et al, 2005) found that (undersulfated) HS was still being made in Ndst1 mutant embryos, we conclude that Ndst1 is responsible for the generation of specific HS structures recognized by the monoclonal antibody 10E4 that are not synthesized by other Ndst isoforms.…”
Section: Ndst1-deficient Embryos Show Reduced Cell Proliferation Incsupporting
confidence: 80%
See 3 more Smart Citations